Perancangan Game Edukasi 2D Tentang Keselamatan di Rumah untuk Anak Usia Dini - Kamilah, Khansa Farah; Slamet Widodo; Rian Rahmanda Putra (Jurnal Teknologi Informatika Multimedia Digital, 2024)
Early childhood is a golden period for children's development to obtain the educational process. This research focuses on designing educational games about safety at home for early childhood. The purpose of this study is to determine the usability feasibility of games based on ISO 9126 standards with indicators namely understandability, learnability, attractiveness and operability. Game development uses the Multimedia Development Life Cycle (MDLC) method which consists of 6 stages, namely: (1) concept, (2) design, (3) material collection, (4) manufacture, (5) testing, (6) distribution. Game testing is done by black box testing techniques. Data analysis in this study used a quantitative analysis method using a questionnaire technique and a Likert scale measurement index. The results of the black box test stated that the game was following expectations because the output reaction was per the input that was carried out. To find out the usability feasibility of the game, a test was conducted on 24 respondents who had siblings or children aged 0 to 6 years who had played educational games. The results of the research that has been done show that game usability is in the very decent category with a percentage of 89.7%. So the educational game about safety at home is made "Very Eligible" in the aspect of usability of the ISO 9126 standard